Caracterización morfológica in situ del tomate de árbol silvestre Solanum spp en las provincias de Loja y Zamora Chinchipe - Lozano Gualán, Henry Patricio (2024)
Ecuador is a megadiverse country in terms of flora and fauna. In the Southern region, specifically in the province of Loja, species with great potential for plant phylogenic improvement have been reported. Wild species of tree tomato are of significant importance due to their ability to adapt to different environmental conditions and their tolerance to disease. Currently, there species are threatened by urbanization, deforestation, and changes in food consumption patterns, highlighting the urgent need for conservation in their natural habitat. The objective of this research was to characterized in situ the wild tree tomato (Solanum spp) in the provinces of Loja and Zamora Chinchipe. A total of 18 plants were characterized using the morphological descriptor for tree tomato and related wild relatives determined by Bioversity International. An Excel database was constructed, and multivariate cluster analysis (dendrograms) was applied for quantitative variable, while bar graphs were used for qualitative variables. The results yielded three clusters, with Cluster 1 standing out for its superior characteristics in terms of fruit weight and number of seeds per fruit. Three wild species of tree tomato were identified in this research: S. cajanumensis, S. circinatum, and S. sp., the latter of which has not been recorded to date.